1995
DOI: 10.1074/jbc.270.7.2993
|View full text |Cite
|
Sign up to set email alerts
|

Glutamic Acid 327 in the Sheep α1 Isoform of Na+,K+-ATPase Stabilizes a K+-induced Conformational Change

Abstract: By combining the tools of site-directed mutagenesis and [3H]ouabain binding, the functional role of glutamic acid 327 in the fourth transmembrane domain of the sheep alpha 1 isoform of Na+,K(+)-ATPase was examined with respect to its interactions with ouabain, Na+,K+,Mg2+, and inorganic phosphate. Using site-directed mutagenesis, this glutamic acid was substituted with alanine, aspartic acid, glutamine, and leucine. The mutant proteins were constructed in a sheep alpha 1 protein background such that [3H]ouabai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 36 publications
4
50
1
Order By: Relevance
“…In addition, Vilsen [12] reported a normal turnover for a Glu327Gln mutant, and even a radical leucine substitution also produced a functional enzyme [ 111. Finally, studies of the non-functional mutants with substitutions at position 327 are consistent with the importance of this site in conformational transitions, but not necessarily in cation binding per se [14].…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…In addition, Vilsen [12] reported a normal turnover for a Glu327Gln mutant, and even a radical leucine substitution also produced a functional enzyme [ 111. Finally, studies of the non-functional mutants with substitutions at position 327 are consistent with the importance of this site in conformational transitions, but not necessarily in cation binding per se [14].…”
Section: Introductionmentioning
confidence: 53%
“…Likewise, transfections with cDNAs carrying the substitutions Aspso8Ala, AspsosAsn and Binding of t3H]ouabain to intact 3T3 cells that were untransfected (3T3) or transfected with a cDNA encoding the wild-type sheep al Na,K-ATPase (WT) or the sheep a-subunit carrying the amino acid substitutions Aspso4Ala (D804A) and AspxflsAla (D808A). Conditions for binding were the same as those described in [14] except that the concentration of [3H]ouabain was 70.6 nM. Data shown are the mean f S.E.M.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Across phylogeny, the Na,K-ATPase ion pump function is contained within the ␣-subunit and depends on an essential aspartic acid that interacts with the terminal phosphate group of ATP to allow hydrolysis of the high-energy bond (reviewed by Kaplan, 2002). Mutation of this invariant aspartic acid to asparagine (D369N in vertebrates) has been shown in several systems to completely abolish ATP hydrolysis and ion pumping (Ohtsubo et al, 1990;Kuntzweiler et al, 1995). Because regions of ␣-subunits containing catalytic function are nearly 100% identical between flies and vertebrates (for example, the 60 residues flanking asparatic acid 369 are 98% identical between fly ATP␣ and the vertebrate ␣-isoforms), it is highly likely that mutation of the essential aspartic acid in fly ␣-subunits completely eliminates ion pump function.…”
Section: Ion-pump-independence Of the Nak-atpase Tube Size And Barrimentioning
confidence: 99%
“…Logical targets of these studies have been carboxyl residues (Glu-327, Glu-779, Asp-804, Asp-808, Asp-926, Glu-953, and Glu-954) 1 that may be located in the transmembrane segments of the protein (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Site-directed mutagenesis studies have shown that substitutions of amino acids Glu-327, Asp-926, Glu-953, or Glu-954 produce no major changes in cation affinity (16 -18, 20) or in the enzyme electrical properties (19).…”
mentioning
confidence: 99%